Sex differences in motor learning flexibility are accompanied by sex differences in mushroom spine pruning of the mouse primary motor cortex during adolescence - Tekin, Michael; Shen, Hui; Smith, Sheryl S. (Frontiers in Neuroscience, 2024)
Although males excel at motor tasks requiring strength, females exhibit greater motor learning flexibility. Cognitive flexibility is associated with a low baseline mushroom spine density, and defective synaptic pruning impairs this process. Therefore, we investigated sex differences in adolescent pruning of mushroom spines in layer 5 pyramidal cells of primary motor cortex (L5M1), a site essential for motor learning. Mushroom spines in proximal L5M1 of female mice decreased by >60% from PND35 (puberty onset) to PND56 (Pubertal: 2.23 ± 0.21 spines/10 μm; post-pubertal: 0.81 ± 0.14 spines/10 μm, P<0.001); male mushroom spine density was unchanged. Because pubertal expression of α4βδ GABAA receptors (GABARs) underlies pruning in other brain regions we determined that pubertal expression of this receptor is greater (P<0.0001) in female L5M1, assessed using immunohistochemistry, and yields tonic GABAergic current, assessed using whole cell patch clamp responses to 100nM gaboxadol, which is selective for α4βδ GABARs. α4 -/-mice did not exhibit mushroom spine pruning, suggesting that α4βδ GABARs also trigger pruning in L5M1. We compared performance of female wild-type mice (low post-pubertal mushroom spine density) with groups displaying higher post-pubertal mushroom spine density (P<0.05, male wild-type, female α4 -/-) on motor learning (constant speed) and learning flexibility (accelerating speed following constant speed) rotarod tasks. Although motor learning was similar for all groups, only female wild-type mice learned the accelerating rotarod task after the constant speed task (P=0.006). These results suggest that sex differences in motor learning flexibility are associated with differences in post-pubertal mushroom spine density in L5M1.